Basic environmental health - Yassi, Annalee (New York ; Oxford : Oxford University Press, 2001)
Drawing from the social sciences, the natural sciences and the health sciences, this text introduces students to the principles and methods applied in environmental health. Topics range from toxicology to injury analysis.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Environmental health